2003
DOI: 10.1159/000071958
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Microglia/Macrophages during Regeneration in the Cerebellum of Adult Teleost Fish, <i>Apteronotus leptorhynchus:</i> A Quantitative Analysis

Abstract: In contrast to mammals, adult teleost fish exhibit an enormous capacity to replace damaged neurons with newly generated ones after injuries in the central nervous system. In the present study, the role of microglia/macrophages, identified by tomato lectin binding, was examined in this process of neuronal regeneration in the corpus cerebelli of the teleost fish Apteronotus leptorhynchus. In the intact corpus cerebelli, or after short survival times following application of a mechanical lesion to this cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Such large condensed fragments cannot be utilized by macrophages/microglia [6]. Similar observations were also identified in morphogenetic study on mammals [20,21].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such large condensed fragments cannot be utilized by macrophages/microglia [6]. Similar observations were also identified in morphogenetic study on mammals [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…However, it remains unknown how the process of reparative neurogenesis correlates with cell proliferation and apoptosis. It was shown that the nervous tissue of fish is restored within a few weeks after injury [6]. The high regenerative potential of these animals is determined by the sequence of some morphogenetic processes, one of them is apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The observed co-localisation of IgMþ cells and nodavirus infected cells in the retina is consistent with this notion. In contrast to mammals, the teleost neurons possess a large regenerative capacity, and the nervous tissues thus have a superior ability to reverse damage [15,16]. The consequences of immunopathology inflicted by local immune responses are therefore likely to be less severe, and this could allow for greater access of immune cells to teleost nervous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The relative absence of immune response in these tissues is linked to the restricted regenerative capacity of mammalian neurons and the prospect of immuno-pathological damage of these vital tissues. In contrast to mammals, the teleost neuron has a remarkable ability to regenerate damaged CNS tissues [15,16], which in turn might permit a more unrestrained immune defence in teleost nervous tissues. Consistent with this notion, relatively high numbers of lymphocytes have been demonstrated in the normal spinal cord of fish [17].…”
Section: Introductionmentioning
confidence: 99%
“…Microglia/macrophages have been identified within a few days after lesions in several divisions of the CNS of teleost fish-the cerebellum [38], the dorsal telencephalon [39,40], and the retina [41]. We used multiphoton confocal microscopy for the in vivo study of early response of microglia/macrophages in the damaged midbrain of juvenile chum salmon Oncorhynchus keta [42].…”
Section: In Vivo Investigation Of Cell Migration After Mechanical Injurymentioning
confidence: 99%